Evaluación del crecimiento y sobrevivencia de Aniba rosaeodora “Palo de rosa” de la plantación N° 38 del CIEFOR - Puerto Almendra, Loreto –Perú. 2022 - Perea Gonzales, Jorge Antonio (2023)
The study was carried out in the forest plantation under twelve of Aniba rosaeodora of CIEFOR - Puerto Almendra. The plants were evaluated in 120 days in order to determine their growth, survival and quality. The plantation presented an average increase in diameter of 1.91 mm. Likewise, the average increase in height of the seedlings was 12.42 cm. The analysis of variance of the increase in height presented a significant difference in the averages (Sig = 0.036). The strips presented a survival of 88.5% (177 live plants), while plant mortality reached 11.5% (23 dead plants). On the other hand, 155 plants presented GOOD quality (87.6%). The quality coefficient of the plantation was from Good to Excellent. It is recommended to carry out permanent and periodic evaluations in order to ensure the success of the plantation over time, as well as to carry out similar studies with other native forest species in CIEFOR - Puerto Almendra.